Construction of a tumor microenvironment pH-responsive cleavable PEGylated hyaluronic acid nano-drug delivery system for colorectal cancer treatment. (5th February 2020) - Zhang, Xinyu; Zhao, Minyi; Cao, Nan; Qin, Wei; Zhao, Meng; Wu, Jun; Lin, Dongjun
Abstract : To improve the tumor cell active targeting, uptake efficiency and circulation time of doxorubicin (DOX) in vivo . Herein, we constructed a cleavable PEGylated hyaluronic acid nano-drug delivery system (HA–mPEG2k –DOX) based on pH-responsive imine bond. Abstract : In order to improve active tumor targeting, tumor cell uptake efficiency and circulation time of doxorubicin (DOX) in vivo, we constructed a cleavable PEGylated hyaluronic acid nano-drug delivery system (HA–mPEG2k –DOX) based on a tumor microenvironment pH-responsive imine bond. In this study, HA–mPEG2k –DOX can self-assemble into stable nanoparticles (HA–mPEG2k –DOX NPs) with a particle size of 50 nm. And the NPs can efficiently target CD44 positive CT26 cells and the pH-responsive cleavable PEG shell can be detached under weakly acidic environments and effectively promote the cellular uptake of HA–DOX NPs. Compared with DOX·HCl, the HA–mPEG2k –DOX NPs can significantly increase the DOX circulation time by 12.5 times, efficiently target the tumor tissues of CT26 tumor-bearing mice and remain for 72 hours. Therefore, the antitumor results in vivo indicated that the HA–mPEG2k –DOX NPs have the best anti-tumor effect while reducing the toxicity of the DOX. Overall, the cleavable PEGylated HA–mPEG2k –DOX NPs responding to pH-sensitive imine bonds, while actively targeting CD44-positive tumor cells, improve the dilemma of cellular uptake and delivery by the PEGylated nano delivery system.